Multidisciplinary Oncovascular Surgery is Safe and Effective in the Treatment of Intra-abdominal and Retroperitoneal Sarcomas: A Retrospective Single Centre Cohort Study and a Comprehensive Literature Review. (November 2020) - Homsy, Pauliina; Blomqvist, Carl; Heiskanen, Ilkka; Vikatmaa, Leena; Tukiainen, Erkki; Numminen, Kirsti; Sampo, Mika; Leppäniemi, Ari; Albäck, Anders; Kantonen, Ilkka; Vikatmaa, Pirkka
Abstract : Objective: Radical excision of retroperitoneal or intra-abdominal soft tissue sarcomas may necessitate vessel resection and reconstruction. The aim of this study was to assess surgical results of retroperitoneal or intra-abdominal sarcomas involving major blood vessels. Methods: This was a retrospective single centre cohort study and a comprehensive review of literature. Patients with retroperitoneal or intra-abdominal sarcomas treated by the oncovascular team in Helsinki University Hospital from 2010 to 2018 were reviewed for vascular and oncological outcomes. A comprehensive literature review of vascular reconstructions in patients with retroperitoneal sarcoma was performed. Results: Vascular reconstruction was performed in 17 patients, 11 of whom required arterial reconstructions. Sixteen of the operations were sarcoma resections; the post-operative diagnosis for one patient was thrombosis instead of the presumed recurrent leiomyosarcoma. Early graft thrombosis occurred in two venous and one arterial reconstruction. Late thrombosis was detected in three (18%). The median follow up was 27 (range 0–82) months. Of the patients with sarcoma resections 5 (31%) died of sarcoma and further 4 (25%) developed local recurrence or new distant metastases. The comprehensive review of literature identified 37 articles with 110 patients, 89 of whom had inferior vena cava reconstruction only. Eight arterial reconstructions were described. Late graft thrombosis occurred in 14%. The follow up was 0–181 months, during which 57% remained disease free and 7% died of sarcoma. Conclusion: Vascular reconstructions enable radical resection of retroperitoneal and intra-abdominal sarcomas in patients with advanced disease. The complex operations are associated with an acceptable rate of serious peri-operative complications and symptomatic thrombosis of the repaired vessel is rare. However, further studies are needed to assess the performance of the vascular reconstructions in the long term.